2001
DOI: 10.1289/ehp.01109s6845
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of endocrine disease among residents of New York areas of concern.

Abstract: There are six Areas of Concern, as identified by the International Joint Commission, located in New York State. Three are contiguous in western New York and have similar contaminants (Buffalo River, Niagara River, and 18 Mile Creek). We used the Statewide Planning and Research Cooperative System database, which records diagnoses according to the (italic)International Classification of Disease, Ninth Revision(/italic) codes for all patients admitted to state-regulated hospital facilities, to compare incidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 39 publications
(14 reference statements)
1
10
0
Order By: Relevance
“…With regard to the route of exposure, the present and our previous observations (Baibergenova et al 2003; Carpenter et al 2001, 2003; Kudyakov et al 2004) are most consistent with air transport of contaminates, both in vapor phase and particulate bound, being the major route of spread, with inhalation of these semivolatile compounds a major (and underappreciated) route of exposure. Ingestion is usually considered to be the most important route of exposure to POPs, but what people eat is not defined by the ZIP code in which they live.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…With regard to the route of exposure, the present and our previous observations (Baibergenova et al 2003; Carpenter et al 2001, 2003; Kudyakov et al 2004) are most consistent with air transport of contaminates, both in vapor phase and particulate bound, being the major route of spread, with inhalation of these semivolatile compounds a major (and underappreciated) route of exposure. Ingestion is usually considered to be the most important route of exposure to POPs, but what people eat is not defined by the ZIP code in which they live.…”
Section: Discussionsupporting
confidence: 88%
“…These compounds alter normal functioning of the immune, nervous, and endocrine systems and are carcinogenic (Carpenter 1998; Lucier 1991; Vine et al 2000). In previous studies, we demonstrated elevated hospitalization for thyroid diseases, diseases of the genital tract, and endometriosis among hospitalized women residing within 15 miles of three areas of concern (AOCs) in western New York (Carpenter et al 2001) and when comparing all ZIP codes containing or abutting POP-contaminated sites with either “other waste” ZIP codes (ZIP codes containing a hazardous waste site but not one containing POPs) or “clean” ZIP codes (ZIP codes that do not contain an identified hazardous waste site) (Carpenter et al 2003). Kudyakov et al (2004) reported a similar elevation in risk of infectious respiratory diseases and chronic bronchitis in POP-contaminated ZIP codes.…”
mentioning
confidence: 99%
“…19 These sites are heavily polluted with numerous chemical agents, including aromatic and halogenated hydrocarbons; residential proximity to these sites has been associated with immune dysfunction 36 and thyroid disease. 37 This study utilized cases from a comprehensive liver transplantation registry to avoid potential referral bias as well as a cohort of untransplanted patients followed at Mount Sinai School of Medicine (New York, NY) in their analysis and identified significant clustering of both groups near SFSs that were open-air dump sites. 19 Although this study was unable to identify specific toxins influencing PBC risk, the authors speculated that exposure to volatile organic compounds (VOCs) such as benzene released from the site may contribute, especially considering the association of cigarette smoking (which contains numerous VOCs including benzene) with PBC and findings that halogenated forms of benzene can mimic the lipoylated autoantigen epitope found in PBC.…”
Section: Geographical Location and Risk Of Primary Biliary Cirrhosismentioning
confidence: 99%
“…Residential proximity to hazardous waste sites has been shown to be positively associated with several adverse health outcomes including thyroid disease, female genital disease, and low birth weight in New York State residents. 17,18 Finally, we also checked the correlation among neonatal outcomes and among maternal perinatal problems using Pearson correlation coefficients. Table 1 shows the frequencies and proportions of sociodemographic factors for the 15,003 cosmetologists and the 4246 Realtors who were matched to birth certificate records during the study period, as well as the 12,171 women selected from the general population.…”
Section: Discussionmentioning
confidence: 99%